A study on service quality provided by government agencies towards achieving customers satisfaction at Urban Transformation Centre (UTC) Melaka / Nur Azni Baharim and Wan Nurul Hidayah Wan Abdul Sobir - Baharim, Nur Azni; Wan Abdul Sobir, Wan Nurul Hidayah (2014)
Project paper titled “A Study on Service Quality Provided By Government Agencies Towards Achieving Customers Satisfaction At Urban Transformation Centre (UTC) Melaka” is conducted as partial requirement to fulfil the requirement as needed by the faculty of Business Management, MARA University of Technology (UiTM). The intention of this study is to identify the service quality provided by agencies in order to achieve customer satisfaction at Urban Transformation Centre (UTC) Melaka. The researcher chooses to use descriptive research design as method and the researcher use survey to gain the data. Data uses in this research are primary and secondary data such as journal and book. Researcher also use questioner to attain the data in order to get the feedback from the visitor/customer who using the services that provided by government agencies at Urban Transformation Centre (UTC) Melaka. The sample size in this research is 100 respondents of visitor at Urban Transformation Centre (UTC) Melaka. Based on the reliability test, respondent profile, frequency, Pearson correlation and multiple regressions, a clear finding and result is observed. The researcher is able to give some recommendations and suggestion and how to improve customer satisfaction at Urban Transformation Centre (UTC) Melaka. The conclusion of this study was the outcome from the survey analysis and findings.